Implementation of Kindergarten Supervisor Academic Supervision - Erna Kusumawati (Ridwan Institute, 2023)
Study This aim For analyse the implementation of supervision academic done by supervisor Kindergarten in East Jakarta. Method which is used in this research is a descriptive qualitative approach. Research design using studies case Which will conducted in one of the Kindergartens in East Jakarta. Results study shows that: (1) Implementation of supervision academic by the supervisor school has fulfil principle supervision implementation academic done with technique supervision individual And group; (2) Act carry on supervision academic by supervisor Kindergarten by providing reinforcement to teachers who have fulfil competency standards and coaching to Teacher which has not been fulfil competency standards.